Biceps Brachii Muscle Fatigue Progression Analysis Using Extended Modified B-distribution Based Time-frequency Features - Karthick, P. A.; Diptasree, Maitra Ghosh; Ramakrishnan, S (CMBES Proceedings, 2017)
No Abstract